Car dependence and housing affordability: An emerging social deprivation issue in London?. (August 2018) - Cao, Mengqiu; Hickman, Robin
This paper investigates the combined problem of high car dependence and housing affordability, in view of likely continued volatility in oil prices (and hence higher petrol and diesel prices), and rising house prices. Household budgets are likely to be stretched where there are high levels of car dependency and housing unaffordability – with little flexibility for rising costs in either or both of these. A composite car dependence and housing affordability (CDHA) index is developed, using indices of oil vulnerability related to car travel and housing affordability. Greater London is used as the case study, with 2001 and 2011 data analysed at the level of Lower Super Output Areas, and presented using Geographic Information System and R statistical software. The findings reveal that there are high levels of composite car dependence and housing price vulnerability in many suburban areas across Greater London, adding to the previous areas of social deprivation found mainly in East London. The composite CDHA index illustrates where the most vulnerable areas are spatially. Many neighbourhoods may become less attractive for those on median or even relatively high incomes. The areas most affected may become much more expensive to live in, potentially leading to much greater pressure on travel and housing costs as people could be forced to live further from the centre of London, including beyond the Greater London boundary, which has further implications for travel. Failing to consider these emerging affordability issues represents an oversight in terms of transport planning in London.